Seriously! : investigating crashes and crises as if women mattered - Enloe, Cynthia H., 1938- (Berkeley : University of California Press, 2013)
In Seriously!, Cynthia Enloe, author of the groundbreaking analysis of globalization, Bananas, Beaches, and Bases, addresses two deeply gendered and contested questions: Who is taken seriously? And who gets to bestow the label ""serious"" on others? With a strategy of taking both women and gender dynamics seriously, Cynthia Enloe investigates the Dominique Strauss-Kahn affair and the banking crash of 2008, the subsequent recession, as well as UN peacekeeping and the ongoing Egyptian revolution. Each case study highlights the gritty experiences of women in diverse circumstances-in banks, on the
8. Egyptian Women, Feminism, Revolutions: The Dinner Party9. Conclusion: In the Eye of the Beholder; Notes; Bibliography; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; R; S; T; U; V; W; X; Y; Z.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Feminism; Feminist theory; Women; Male domination (Social structure); Financial crises; Feminism; Women; Féminisme.; Théorie féministe.; Femmes; Domination masculine (Structure sociale); feminism; women (female humans); SOCIAL SCIENCE -- Feminism & Feminist Theory; SOCIAL SCIENCE -- Gender Studies; Feminism; Feminist theory; Financial crises; Male domination (Social structure); Women; 2008.; america; anthropology; banking crash; banking; case studies; cultural criticism; current events; dominique strauss kahn; egyptian revolution; female experience; feminism; feminist theory; gender dynamics; gender politics; gender studies; job market; modern women; nonfiction; postwar era; recession; revolutionary women; revolutions; risk taking; seriousness; sexual harassment; taken seriously; un peacekeeping; war zones; womens issues; womens security; worth; Electronic book